HAZARD IDENTIFICATION AND PREVENTION METHODS ON WORK IN CONFINED SPACES - Sulardi, Sulardi; El-Ridho, Nuruddin Kafy (IDENTIFIKASI, 2019)
The purpose of this study is to provide an overview of potential hazards and safe work procedures in the confined space area of ​​the working of the oil and gas industry. The research method used was the application research method with a case study approach in the oil and gas industry in Balikpapan. The results showed that the potential danger in the room was limited by the danger of lack of oxygen, fire, poisoning explosion, irritation, static electricity, mechanical energy, extreme room temperature, dehydration, insufficient air circulation, slippery surfaces and ergonomic hazards. Safe working procedures in confined spaces were ensuring a safe working environment, use of PPE and work safety equipment, isolation of mechanical equipment, cleaning of gases and liquids, adequate air ventilation and adequate communication systems. The results of the study also recommended supporting the success of work in the confined space area to always be aware of the possibility of toxic gas, low oxygen concentrations and excess, the danger of work equipment and workers equipped with a gas tester.